2014
DOI: 10.1016/j.biochi.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microsomal triglyceride transfer protein in lipoprotein-synthesizing tissues of the developing chicken embryo

Abstract: In contrast to mammals, in the chicken major sites of lipoprotein synthesis and secretion are not only the liver and intestine, but also the kidney and the embryonic yolk sac. Two key components in the assembly of triglyceride-rich lipoproteins are the microsomal triglyceride transfer protein (MTP) and apolipoprotein B (apoB). We have analyzed the expression of MTP in the embryonic liver, small intestine, and kidney, and have studied the expression of MTP in, and the secretion of apoB from, the developing yolk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
2
11
0
1
Order By: Relevance
“…Similarly, in D. melanogaster , MTP transcripts were found in the fat body (an organ analog to vertebrate adipose tissue and liver), and MTP proteins are reported to promote the production of Lpp and large lipid transfer particles ( 14 ). MTP transcripts were also found in vertebrates in tissues expressing apoB, such as liver, intestine, retina ( 45 ), kidney ( 46 ), myocardium ( 47 ), placenta, and yolk sac ( 48 – 50 ). Here, MTP functions as an essential chaperone for the assembly and secretion of apoB-lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in D. melanogaster , MTP transcripts were found in the fat body (an organ analog to vertebrate adipose tissue and liver), and MTP proteins are reported to promote the production of Lpp and large lipid transfer particles ( 14 ). MTP transcripts were also found in vertebrates in tissues expressing apoB, such as liver, intestine, retina ( 45 ), kidney ( 46 ), myocardium ( 47 ), placenta, and yolk sac ( 48 – 50 ). Here, MTP functions as an essential chaperone for the assembly and secretion of apoB-lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that ACRB expressed higher levels of Apo-B and MTTP on E18 when compared to COBB. MTTP plays an important role in synthesis, translocation and secretion of Apo-B-containing lipoproteins in the cell [29]. This result may be partially explained by the fact that ACRB utilizes more yolk than COBB as described above.…”
Section: Discussionmentioning
confidence: 96%
“…This result may be partially explained by the fact that ACRB utilizes more yolk than COBB as described above. Some evidence showed that Apo-B also highly expressed in the yolk sac during embryonic development [29]. However, we only investigated the gene expression in the liver in this study.…”
Section: Discussionmentioning
confidence: 99%
“…GM3, as a suppressor of cellular TG synthesis and secretion, directly downregulated the level of MTP synthesis. MTP known as a target for the inhibition of ApoB secretion is essential for the hepatic secretion of ApoB‐containing lipoprotein [Ivessa et al, ; Eresheim et al, ; Lee and Hegele, ] by mediating the transfer of TG to nascent ApoB. Because GM3 inhibits ApoB secretion and transcriptional activity of MTP, assembly and secretion of VLDL in liver cell are largely controlled by newly synthesized ApoB.…”
Section: Discussionmentioning
confidence: 99%